A reconciling vision of the Adriatic-Ionian Bimodal Oscillating System - Gian Luca Eusebi Borzelli; Sandro Carniel (Scientific Reports, 2023)
Abstract The bimodal oscillating system (BiOS) consists in an oscillation of the Ionian Sea surface structure with period of 12–13 years, which reflects in a near-surface circulation inversion. BiOS regimes are deeply interconnected with the circulation patterns of the Eastern Mediterranean, and it is a dominant process governing water masses formation, air-sea fluxes and bio-geochemical properties, which impacts living organisms. The BiOS has been partially explained as a self-sustained oscillation maintained by the interplay between Adriatic dense water formation and changes in the relative volume of waters of Levantine and Atlantic origin entering the Adriatic; however, attempts have also been made to explain the BiOS in terms of atmospheric-related processes. Despite the intensive research aiming at reproducing this oscillating system, the fundamental question “which is the source of energy necessary to initiate the BiOS?” has, until now, remained unanswered. The scope of this paper is two-fold. First, we document that, since 1993, two periods in the BiOS can be observed: a first one, between 1993 and 2017, during which the BiOS damped up to nearly disappear, with e-folding time of 11 years; and a second one, starting in 2017, during which the BiOS revitalized. Then, we propose here an analytical model that, under a two-layer ocean assumption, shows how it is possible for winds rotating in the same direction to initiate oscillations of the free surface, as result of the competing effects of wind and internal fluid pressure fields. The proposed model forced with wind data could successfully reproduce the characteristic time scales of the BiOS cycle over the period 1993–2019, and is therefore offered as a novel vision explaining the originating mechanism as the basis of its initiation, as well as a fundamental tool to address possible BiOS regimes in future climate scenarios.